ASAS KELANGSUNGAN USAHA SEBAGAI LANDASAN FILOSOFIS PERLINDUNGAN HUKUM BAGI DEBITOR PAILIT SEHUBUNGAN TIDAK ADANYA INSOLVENCY TEST DALAM PENYELESAIAN SENGKETA KEPAILITAN - Aprita, Serlika (Universitas Islam Negeri Raden Fatah Palembang, 2017)
In its development, the Bankruptcy Law in theory and practice did not progress significantly and it was until 1998 and replaced by a new one, which on October 18, 2004 legalized bankruptcy law and postponement of debt obligations have a wider scope, this is necessary because of the development and legal needs in the community while the provisions that have been applied is not sufficient as a legal means to solve the problem of accounts receivable in a fair, fast, open, and effective. One of them concerning the requirement to declare a bankrupt debtor as stipulated in the provisions of Article 2 paragraph 1 that there is no provision that requires the debtor to be insolvency, this is certainly contrary to the universal philosophy of the Bankruptcy Act that provides a way out for debtors and creditors when the debtor is in a state unable to pay its debts. The absence of this insolvency test shows that the Bankruptcy Act is dominant in protecting the interests of creditors. In order to have a clear philosophical foundation, the concept of business continuity principles should be included in the future Article of Bankruptcy Regulation so as to enable debtor and creditors to pursue debt settlement fairly, quickly, openly and effectively. The type of research in the writing of this journal is prescriptive normative legal research.